Anatomical and microstructures features of tropical bamboo Gigantochloa brang, G.levis, G.scotechinii and G.wrayi - Razak Wahab; Mohd Tarmizi Mustafa; Mahmud Sudin; Othman Sulaiman (2011)
Anatomical and microstructure studies on four of cultivated tropical bamboo species of genus Gigantochloa were studied. Gigantochloa brang, G. levis, G. scotechinii and G. wrayi of age-group 3 were selected, harvested and processed for use in the studies. The studies focussed mainly on the vascular bundles and fibers located at the internodes and nodes at the outer, middle and inner sections of the bamboo culm wall. The sizes of the vascular bundles length, vascular bundles width, fiber length, fiber diameter, fiber lumens diameter, fiber walls thickness and fiber Runkle’s ratio were measured between each of the species in relation to the samples positions at the internodes, nodes, and positions in the crosssection of the bamboo culms. The results in the fibers morphology studies showed that the fibers for each species have different lengths, diameters, cell walls thickness and lumen sizes. The size of vascular bundle is smaller at outer position and becomes bigger at the inner position. All the four (4) bamboo species exhibited similar in characteristics but their anatomical features and microstructures were different.